2015
DOI: 10.1007/s10616-015-9895-4
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds and cells for tissue regeneration: different scaffold pore sizes—different cell effects

Abstract: During the last decade biomaterial sciences and tissue engineering have become new scientific fields supplying rising demand of regenerative therapy. Tissue engineering requires consolidation of a broad knowledge of cell biology and modern biotechnology investigating biocompatibility of materials and their application for the reconstruction of damaged organs and tissues. Stem cell-based tissue regeneration started from the direct cell transplantation into damaged tissues or blood vessels. However, it is diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
391
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(433 citation statements)
references
References 105 publications
(114 reference statements)
8
391
1
Order By: Relevance
“…The scaffold showed a well ordered and interconnected porous structure. It was considered that the pore size of scaffolds should be large enough to ensure nutrient delivery and tissue ingrowth but not too large to prevent cell migration [30] . Roosa et al [31] found all of the polycaprolactone scaffolds with pore size from 350 to 800 μm could promote bone regeneration and there were no significant differences in new bone formation between them.…”
Section: Resultsmentioning
confidence: 99%
“…The scaffold showed a well ordered and interconnected porous structure. It was considered that the pore size of scaffolds should be large enough to ensure nutrient delivery and tissue ingrowth but not too large to prevent cell migration [30] . Roosa et al [31] found all of the polycaprolactone scaffolds with pore size from 350 to 800 μm could promote bone regeneration and there were no significant differences in new bone formation between them.…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that the degrees of cell migration and sprouting of blood vessels into three‐dimensional (3D) porous scaffolds depend on the pore size of scaffolds . Although the pore size most suitable for subepithelial tissue formation and angiogenesis in the tracheal mucosa is unknown, many reports have suggested that 3D scaffolds enriched with >100‐μm pore diameters are beneficial for cell invasion . In our study, it was difficult to measure the pore sizes of the bovine collagen sponges, but the intermembrane spaces in the 0.7% sponge appeared to be larger than those in the 0.5% and 1.0% sponges.…”
Section: Discussionmentioning
confidence: 65%
“…This is required to maintain the structural integrity and the length of the affected limb. The newly formed pore channels in the PCL skeleton will help in the formation of the vascular network and therefore, facilitate the supply of oxygen and nutrients to the cells growing deep inside the scaffolds …”
Section: Discussionmentioning
confidence: 81%